Creating a culture of prevention in occupational safety and health practice: perceived body discomfort in two sitting positions - Ezrin Hani, Sukadarin; Junaidah, Zakaria; Qian, F. S; Nur Syazwani, Mohd Nawi; Baba, M. Deros (Malaysian Public Health Physicians’ Association, 2018)
Prolonged sitting is one of the factors for back discomfort. Sitting in the same position for long periods of time is worse. This experimental based study was conducted to achieve three objectives. There were to 1) identify whether is there any differences between perceived body discomfort among respondents before and after upright sitting, 2) identify whether is there any differences between perceived body discomfort among respondents before and after slump sitting and 3) compare the level of perceived body discomfort among respondents after two sitting postures. Thirty young and healthy adults were recruited as study respondents. Each respondent was asked to sit in a posture either upright or slump for 30 minutes. Respondents were then rated their body discomfort using Borg CR-10 scale before and after sitting. Another sitting posture was carried out after one day interval. There is a significant difference between perceived body discomfort among respondents before and after upright and slump sitting. Body discomfort of upright sitting was shown significantly greater than slump sitting. Although, slump sitting caused less discomfort than upright, but it proven by previous studies did not provide benefit to occupational safety and health practice in preventing occupational health related disease.